National survey to determine current practices, training and attitudes towards advanced polypectomy in the UK. Issue 2 (3rd December 2014) - Geraghty, Joe; O'Toole, Paul; Anderson, John; Valori, Roland; Sarkar, Sanchoy
Abstract : Objective: Developments in advanced polypectomy technique provide an alternative to surgery in the management of large and complex colorectal polyps. These endoscopic techniques require expertise and can potentially incur high complication rates. This survey evaluates current UK practice, attitudes and training in advanced polypectomy. Design: Anonymous online questionnaire. Setting: Colonoscopists within the UK were asked about their approach to large polyps (>2 cm). Results: Among the 268 respondents (64% of whom were BCSP accredited), 86% were confident in removing lesions >2 cm by endoscopic mucosal resection (EMR). Of these, 27% were classed as low volume operators (<10 lesions resected/annum) and 14% as high volume operators (>50/annum). By comparison, only 3% currently performed endoscopic submucosal dissection (ESD). Referring one or more benign polyps for surgery a year was common among responders of all levels (11–68%). Training deficiencies were common: only 21% of responders had received a period of training dedicated to advanced polypectomy; 58% of responders would welcome a national training scheme and a majority supported the implementation of advanced polypectomy accreditation with national guidelines. However, while 41% wanted nominated regional EMR experts, only 18% would welcome an integrated national referral network for large/complex polyps. Conclusions: EMR is practised widely while ESD service provision is very limited. Most experienced colonoscopists are confident to perform piecemeal EMR, even if their training is suboptimal and annual numbers low. Practices and attitudes were variable, even among self-defined level 4 operators. Improving training and implementation of accreditation were welcomed, but there was little appetite for mandated referral to subspecialist 'experts' and national networks.